Efektivitas Penggunaan Aplikasi Daring, Video Conference Dan Sosial Media Pada Mata Kuliah Komputer Grafis 1 Di Masa Pandemi Covid-19 - Rustaman, Abdul Haris (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Covid-19 the Impact of application learning patterns in the world of education. This also occurs in the computer graphics 1 corses of Visual Communication Design Program, Trilogi University Jakarta. The process of delivering lecture material switches from offline to perfectly digital online by utilizing educational-based applications by Edmodo, Google Meet, and Instagram as supporters to display the final Exam. The purpose of this study was to determine the level of understanding of students in using the application. The research method used is qualitative by looking at the highest percentage of respondents (students) who use the application. The results of this study are expected to be a benchmark or input in the teaching and learning development process in the coming semester program.